Personal retirement advisory tool with income classification in Malaysia - Lim, Xin Jie (2023)
This project is a design and development project on retirement advisory tools for Malaysia citizen. It involves methodology, concept, and design of a financial decision-making tool with the focus on retirement planning financial areas. This personal retirement advisory tool will be developed as a mobile application due to more efficient and available for offline using. The development project will use some calculation and algorithms to calculate and estimate the amount of money needed for user’s retirement life. The factors such as inflection, lifestyle, insurance, saving and other more that play an important role on effecting future money flow will be consider in the calculation. A suitable recommendation will be given to the user as reference on their financial planning according to the studies of users’ data and research. The recommendation provided hope to help user having a better plan and understanding on money flow during retirement and have planning as soon as possible once they step in work field.